Effects of monetary and macro-prudential policies – evidence from inflation targeting economies in the Asia-Pacific region and potential implications for China - Soyoung Kim; Aaron Mehrotra (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
We examine the effects of monetary and macroprudential policies in the Asia-Pacific region, where many inflation targeting economies have adopted macroprudential policies in order to safeguard financial stability. Using structural panel vector autoregressions that identify both monetary and macro-prudential policy actions, we show that tighter macroprudential policies used to contain credit growth have also had a significant negative impact on macroeconomic aggregates such as real GDP and the price level. The similar effects of monetary and macroprudential policies may suggest a complementary use of the two policies at normal times. However, they could also create challenges for policy-makers, especially during times when low inflation coincides with buoyant credit growth.
URN:NBN:fi:bof-201703061175
Keywords: E58; E61; 330